Challenges and prospects for pharmacotherapy in functional gastrointestinal disorders. - Sanger, G; Chang, L; Bountra, C; Houghton, L (2010)
Functional gastrointestinal disorders, such as irritable bowel syndrome and functional dyspepsia, are complex conditions with multiple factors contributing to their pathophysiology. As a consequence they are difficult to treat and have posed significant challenges to the pharmaceutical industry when trying to develop new and effective treatments. This review provides an overview of these difficulties and how the industry is reshaping its drug developmental strategies. It describes some of the more significant and encouraging advances that have occurred, and discusses how future research might embrace the opportunities provided by advances in genetic and in particular, epigenetic research.